If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + 4) = 3x + 12 Reorder the terms: 2(4 + 2x) = 3x + 12 (4 * 2 + 2x * 2) = 3x + 12 (8 + 4x) = 3x + 12 Reorder the terms: 8 + 4x = 12 + 3x Solving 8 + 4x = 12 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 8 + 4x + -3x = 12 + 3x + -3x Combine like terms: 4x + -3x = 1x 8 + 1x = 12 + 3x + -3x Combine like terms: 3x + -3x = 0 8 + 1x = 12 + 0 8 + 1x = 12 Add '-8' to each side of the equation. 8 + -8 + 1x = 12 + -8 Combine like terms: 8 + -8 = 0 0 + 1x = 12 + -8 1x = 12 + -8 Combine like terms: 12 + -8 = 4 1x = 4 Divide each side by '1'. x = 4 Simplifying x = 4
| 18x^2-132x+242=0 | | 8(x+1)-11=53 | | x+0.068x= | | x+x+5+2(x+5)=431 | | 3x+-14=x | | a^2-15a-40=0 | | 33-4x=2x-3 | | 6y=4-12 | | 3a/4-7/4=4a/3+5/3 | | 3x+10=17+2x | | x+0.068= | | m^2+7m-12= | | 7/3=2w | | 4(x+1)-11=53 | | 5(x+1)-11=53 | | -6(x+1)-11=53 | | 60=-16x^2+85x | | x+2/3-1/2=x/3-2(x-2)/3 | | -3x-3(-5x-17)=17 | | -4h+16=22+2 | | 12+2(3p-4)=22 | | 11-6m-20=20-5m | | 5x+3=6x-14 | | 3b+2(b-3)=91.50 | | 8x-(-2+3)=11 | | 1/4(x-4)+x=14 | | 6x-12-3=x+27-9x | | 5/10+7/3 | | (2x-3)(x^3-x^2+3x+5)=0 | | 2x-2x+3=8 | | 72/x=8 | | 7=6q/4+8/4 |